Learning and collaboration technologies : third international conference, LCT 2016, held as part of HCI International 2016, Toronto, ON, Canada, July 17-22, 2016, proceedings /: third international conference, LCT 2016, held as part of HCI International 2016, Toronto, ON, Canada, July 17-22, 2016, proceedings. (2016) - Unknown
No abstract available